Keterkaitan Lembaga Keuangan Mikro Syariah Dengan Agenda Sustainable Development Goals (SDGs) - Trimulato, Trimulato; Nuringsih, Nuringsih (Universitas Islam Negeri Alauddin Makassar, 2019)
In February 2018, growth of financing by 52.9 percent. Islamic microfinance institutions have a role in increasing people's economic income. The goal sustainable development or commonly called Sustainable Development Goals (SDGs), its have 17 goals achieved until 2030. Goals is bring prosperity all levels society. It is line with existence Islamic microfinance institutions to improve standard living and public welfare. Type this paper is qualitative method, used is qualitative descriptive analysis, describes growth Islamic microfinance institutions BPRS and BMT institutions. Describes SDGs have objective conformity with BPRS and BMT. Results this paper indicate growth Islamic microfinance institutions, where there are component BPRS grow 10 percent. Results show are financing aspects grow 17.1 percent. BMT financial ratio remaining operating grew by 403.5 percent. Study provides information that Islamic financial institutions are accordance with achievement program SGDs related increasing income and economic activities can realized with presence welfare. Form role sharia financial institutions, easy access capital and socialization introduction financial investment.Keywords : BPRS, BMT, and Sustainable Development Goals (SDGs), Islamic microfinancePada Februari 2018 pertumbuhan pembiayaan menunjukkan yang tumbuh sebesar 52,9 persen. Lembaga keuangan mikro syariah memiliki peran dalam meningkatan pendapatan ekonomi masyarakat. Tujuan dari pembangunan berkelanjutan atau yang biasa disebut Sustainable Development Gols (SDGs). SDGs memiliki 17 tujuan yang ingin dicapai sampai tahun 2030. Tujuan ini sejalan dengan keberadaan lembaga keuangan mikro syariah untuk meningkatkan taraf hidup masyarakat dan meningkatkan kesejahteraan. Artikel ini menggunakan metode kualitatif dengan teknik deskriptif, menguraikan pertumbuhan lembaga keuangan mikro syariah yaitu BPRS dan BMT. Yang dikaitkan Sustainable Development Goals (SDGs). Hasil menunjukkan pertumbuhan lembaga keuangan mikro syariah, beberapa komponen pada BPRS tumbuh di atas 10 persen. Pertumbuhan pembiayaan tumbuh sebesar 17,1 persen. Sisa hasil usaha yaitu sebesar 403,5 persen. Peran lembaga keuangan syariah dalam pencapaian SGDs meningktakan pendapatakn dan usaha masyarakat untuk menghadirkan kesejahteraan. Melalui akses keuangan baik dalam bentuk memberikan kemudahan akses modal dan pengenalan produk investasi, masyarakat dapat meningkatkan pendapatan.Kata Kunci: BPRS, BMT, Sustainable Development Goals (SDGs), Keuangan Mikro Syariah